A captive church: Catholicism and repression in Vietnam - Mais, Jean (Indochina report, 1988)
The secretary-general of the Vietnamese communist Party (VCP) promised at the Sixth VCP Congress in late 1986 to take measures to respect religious freedom and to improve relations with the Catholic Church. According to the author, however, recent developments suggest otherwise. Persecutions have continued. He explains in this essay how the Church is kept captive by the communist regime. (DÜI-Sen)